2020
DOI: 10.1021/acs.est.0c01805
|View full text |Cite
|
Sign up to set email alerts
|

Mother to Fetus Transfer of Hydroxylated Polychlorinated Biphenyl Congeners (OH-PCBs) in the Japanese Macaque (Macaca fuscata): Extrapolation of Exposure Scenarios to Humans

Abstract: Prenatal hydroxylated polychlorinated biphenyls (OH-PCBs) exposure may disrupt fetal brain development during the critical period of thyroid hormone (TH) action. However, there are limited studies on the OH-PCB transfer to the fetal brain, particularly in primates. In this study, we selected the Japanese macaque (Macaca fuscata) as a model animal for the fetal transfer of OH-PCBs in humans and revealed OH-PCB concentrations and their relationships in maternal and fetal blood, liver, and brain. l-thyroxine (T4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
(71 reference statements)
0
5
0
Order By: Relevance
“… 47 Laboratory studies also implicate OH-PCBs in neurotoxic outcomes. 33 , 48 While OH-PCBs have been reported in animal brain tissue, 49 , 50 it is currently unknown whether OH-PCBs are present in the human brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 47 Laboratory studies also implicate OH-PCBs in neurotoxic outcomes. 33 , 48 While OH-PCBs have been reported in animal brain tissue, 49 , 50 it is currently unknown whether OH-PCBs are present in the human brain.…”
Section: Introductionmentioning
confidence: 99%
“…For example, maternal exposure to OH-PCBs during pregnancy may increase neonatal T4 levels . Laboratory studies also implicate OH-PCBs in neurotoxic outcomes. , While OH-PCBs have been reported in animal brain tissue, , it is currently unknown whether OH-PCBs are present in the human brain.…”
Section: Introductionmentioning
confidence: 99%
“… 71 Similarly, X1-OH-PCB52 and 4-OH-PCB52 were detected with a detection frequency of 20% in the rat brain 3 weeks after an intraperitoneal administration of a high PCB52 dose (100 mg/kg bw). 66 PCBs and OH-PCBs have also been detected in the brain of Macaca fuscata , with levels ranging from 6.7 to 31 pg/g, 72 and in a small number of post-mortem human brain tissue samples. 19 While OH-PCBs have been reported in the brains of exposed mammals following longer repeated exposures, our study indicates acute exposures may not be sufficient for metabolizing and detecting OH-PCBs in the brain.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative models also showed that OH-PCBs may competitively bind with TTR, resulting in aggregation of FTHs . The presence of OH-PCBs also suppressed T3-induced transcriptional activation of TRs and led to aggression of T3 in Japanese macaque ( Macaca fuscata ) . Additionally, 2,3,3′,4′,5-pentachloro-4-biphenylol (4-OH–CB-107) and 2,2′,4,4′,5,5′-hexachloro-3-biphenylol (3-OH-CB-153) were found to abolish the inhibitory effects of dexamethasone on T3 secretion and T4 to T3 conversion in chicken liver, thereby promoting T3 production.…”
Section: Discussionmentioning
confidence: 99%
“…195 The presence of OH-PCBs also suppressed T3induced transcriptional activation of TRs and led to aggression of T3 in Japanese macaque (Macaca f uscata). 219 Additionally, 2,3,3′,4′,5-pentachloro-4-biphenylol (4-OH−CB-107) and 2,2′,4,4′,5,5′-hexachloro-3-biphenylol (3-OH-CB-153) were found to abolish the inhibitory effects of dexamethasone on T3 secretion and T4 to T3 conversion in chicken liver, 220 thereby promoting T3 production. Meanwhile, 4-OH-CB-107 in human infant had positive association with T4 and T3 levels, showing a consistent trend with toxicological studies.…”
Section: Hyperthyroidism Risk Chemicalsmentioning
confidence: 99%